Khawarij and the Sunnah of the Prophet: Genealogy of Inkar al-Sunnah in the Early History of Islam - Taufik, Wildan; Wendry, Novizal; Majid, Abdul; Isnaeni, Ahmad (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2018)
This article discusses the Khawarij sect and the Sunnah of the Prophet. The discussion focuses on the genealogy of the Ink?r al-Sunnah movement during the early period of Islamic history. Using a literature review method, this article finds that, as an early Islamic sect, the Khawarij were not only a physical rebellion movement but also transformed into an intellectual movement. This article concludes that one of the intellectual products of the Khawarij sect is the dictum